Vaccine Covid-19 Carrier Box Menggunakan Modul Thermoelectric Cooler Dan Heat Pipe Sebagai Alternatif Alat Distribusi Vaccine Covid-19 - Stevan Graciano Boyana; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Secretary General of the Ministry of Health (Kemenkes) Oscar Primadi stated that the obstacle in distributing the covid-19 vaccine in Indonesia is that there are still many remote areas that are difficult to access by vehiclesthat have cooling rooms such as planes, ships or box cars equipped with refrigeration boxes. In this study discussed about the design of vaccine carrier box using thermoelectric cooler module and heat pipe as analternative distribution tool vaccine covid-19 where thermoelectric cooler used is type TEC2-25408 which is coupling with heat pipe made of copper with working fluid is water. Excellent heat absorption by heat pipe isthe reason for this study. When heat flux heat pipe evaporator operation is achieved and able to absorb heat disposed heat side TEC then the heat side temperature can be maintained constantly, so the workload of TECcan be reduced and the use of the number of peltier elements and power can be reduced. The result of this study is the design and manufacture of vaccine carrier box measuring 36.5 cm x 22 cm x 21 cm based on emptybunches of palm oil capable of carrying 100 vials of covid-19 vaccine in accordance with sop distribution of vaccine 2-8 °C by using peltier elements type TEC2-25408 which is coupling with heatsink heat pipe as acooling system. Based on the test obtained the highest experimental COP value of 0.314 and design COP of 0.364 with a difference of 0.0492 or 13.5 %Keywords: vaccine carrier box, 2-8°C, thermoelectric cooler, heat pipe, COP, saving power